Nutrient Characterization of Cassava Plant Meal and Effects of Feed Additives on its Utilization by Broiler Chickens at Starter and Finisher Phases - Tinuala, Jacob Akintunde (2015)
The study was designed to determine the nutrient composition of cassava plant meal (CPM) and to evaluate the utilization of CPM with or without feed additives by broiler chickens at starter and finisher phases. The aim was to substitute maize with CPM because maize is becoming unavoidable for poultry farmers due to competition between man and his livestock for maize.